The meaning of universality in the Indonesian Idol television program format - Benedictus Arnold Simangunsong; Gamaliel Paulus Setianugraha (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2024)
Competition between television in Indonesia encourages the existence of a television program planning strategy, mainly to buy the concept of a television format that has been successful in other countries by adopting its success. Of course, the adoption that is carried out requires adaptation to the culture that exists in a country, in this case, through research on the Indonesian Idol event. When adaptation occurs and there are local factors such as the cultural, psychological, and physical factors of the audience, it is at that point that it is questionable whether it is about the meaning of the universality of an adopted show program. With case study methods and constructivism paradigms, as well as data collection through interviews with key informants from Freemantle, RCTI, and the audience. From the data processing, it was found that the meaning of universality is divided into three categories, namely, competition, narrative, and participation, and the meaning of emotion has two categories, namely, as a response and as an effect of contagion.